The Effect of Giving Extract African Catfish Meat (Clarias Gariepinus) on the Length of Time for Cuts Healing Process among White Male Wistar Rats (Rattus norvegicus) - Pidyastuti Pakaya; Rini Daud Supu; Multiani S. Latif (LPPM Universitas Bina Mandiri Gorontalo, 2021)
African catfish is one of the freshwater fish with high albumin which plays a role in the process of new cell formation, so that, it can help the process of cell growth and can accelerate the healing of damaged skin cells due to an incision. This study aims to find out the effect of giving extract African Catfish meat on the length of time for the cuts healing process and the dose of African catfish extract that can provide the best effect in the cut healing process is given orally. This research is a laboratory experimental study with a cross-sectional research design with a post-test only control group design using 20 white rats as research subjects which were divided into a 25 ml dose treatment group, 50 ml, and 75 ml/200 grBB rats and negative control. Observations of cuts healing were carried out macroscopically with the parameters of reduced redness and edema and measuring the length of the incision using a ruler. Data analysis used the Kruskal walis test and post hoc test, the results of the analysis showed that there was a significant difference (p<0.05) between the negative control group and the P1, P2, and P3 groups. This shows that African Catfish meat extract affects wound healing. The P3 group (75 ml extract) had more effect on the cuts healing process than the P1 group (50 ml extract) and the P2 group (50 ml extract).